Social Bonds Across Immigration Generations and the Immigrant School Enclave: A Multilevel Longitudinal Study of Student Violence, School Disorder, and Dropping Out, United States, 2002 - Peguero, Anthony ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed. This study consists of a secondary analysis of data from the Educational Longitudinal Study of 2002 (ELS) to investigate associations between immigration, misbehavior, victimization, disorder, and educational failure (i.e., dropping out). Six research questions that were addressed in this study include: do school social bonds vary across immigration generations? Second, is student violence (i.e., misbehavior and victimization) explained by school social bonds across generations? Third, are student violence and school disorder related to the children immigrants' likelihood of dropping out? Fourth, are strong school social bonds mitigating the likelihood of dropping out for the children of immigrants? Fifth, are immigrant school enclaves associated with increased school social bonds among adolescents, decreased student violence and school disorder, and lower levels of dropping out? Sixth, does the intersection of race, ethnicity, and gender moderate the relationship between student violence and school social bonds for the children of immigrants?There are no data files available with this study. Only the syntax file used by the researcher is provided.